AI Ethics as Applied Ethics - Hallamaa, Jaana; Kalliokoski, Taina (Frontiers in Computer Science, 2022)
The need to design and develop AI in a sustainable manner has motivated researchers, institutions, and organizations to formulate suggestions for AI ethics. These suggestions cover various topics and address diverse audiences, but share the presupposition that AI ethics provides a generalizable basis for designers that is applicable to their work. We suggest that one of the reasons, why the influence of current ethical codes has remained so modest, may be the conception of applied ethics that they represent. We discuss bioethics as a point of reference for weighing the metaethical and methodological approaches adopted in AI ethics, and suggest that AI ethics could be made more methodologically solid and substantively more influential if the resources were enriched by adopting tools from fields of study created to improve the quality of human action and safeguard its hoped-for outcomes. The approaches we consider to be useful for the purpose are the systems theory, safety research, the impact assessment approach, and the theory of change.